Homegrown hate : why white nationalists and militant Islamists are waging war against the United States - Kamali, Sara, 1984- (University of California Press, 2021)
"Why are American citizens--white nationalists and militant Islamists--committing acts of terrorism against their own country? What are their worldviews and how do they compare? Why is the current counterterrorism paradigm not working, and what can be done to address this increasingly transnational peril from within? Homegrown Hate is a groundbreaking and deeply researched work that directly juxtaposes militant Islamism and white nationalism in the United States. By examining the self-described grievances, beliefs, and rationales of the individuals who subscribe to these ideologies and detailing their respective organizational structures, scholar and activist Sara Kamali provides compelling insight into the true threat to homeland security: American citizens who are targeting the United States in accordance with their respective narratives of holy war. She expertly explains what can be done, lucidly providing hope in uncertain and divisive times. Innovative and engaging, Homegrown Hate is an indispensable resource for students, policy makers, and anyone who cares about the future of the United States"--